Prevalence of vaping, vaping-associated short-term symptoms of respiratory and cardiovascular morbidities, and factors associated with the initiation of vaping among young adults in Kuwait - Aisha Altanaib; Arwa Alkhannah; Dhuha Alfouderi; Mariam Almutairi; Rawan Abdullah; Maryam Almuhaileej; Fajer Alqadeeri; Reema Alajmi; Loulwah Alenizi; Ahmad Alsultan; Saeed Akhtar (Tobacco Induced Diseases)
Introduction E-cigarette use or vaping is a public health concern, especially among young adults worldwide. This cross-sectional study aimed to: 1) assess the prevalence of vaping among young adults; 2) assess the prevalence of short-term vaping-associated respiratory and cardiovascular symptoms; and 3) identify factors associated with vaping status among a student population in Kuwait.